جماليات التنغيم ودلالاته في قصيدة" الشاعر والملك الجائر" لإليا أبي ماضي - شكورة, ليلى (جامعة الوادي - university of eloued, 2024)
اللّغة العربية لغةٌ موسيقيّة بامتياز، فهي لغة غنائية، تتناغم وحداتها وتتآلف مكوّنة مقاطع موسيقية بديعة، وشِعرها المنبثق عنها يحمل بين طياته خصائصها وميزاتها فهو؛ يتميّز بوحدة صوتية ودلالية قمة في الانسجام والتآلف. يسعى هذا المقال إلى تقّفي مناحي الجمال الإيقاعي المنبثق عن النغم الشعري في قصيدة "الشّاعر والملك الجائر" لإليا أبي ماضي، وتحليل آثار هذا النمط الفني الفريد، الذي يختزل موسيقى الحياة، عبر توقيعات الأنغام والأوزان والقوافي. The Arabic language is distinguished by its richness of musical rhythm, It is a lyrical language, Its units harmonize, forming a wonderful piece of music, And her poetry that emanates from it carries with it its characteristics and features. It is characterized by vocal and semantic unity, a peak in harmony and harmony, and its internal and external music gives it eloquence and the power of influence on the listeners. This article seeks to trace the aspects of the rhythmic beauty emanating from the poetic melody in the poem "The Poet and the Unjust King" by Elia Abi Madi, and to analyze the effects of this unique artistic style, which reduces the music of life, through the signatures of melodies, meters and rhymes.
The Aesthetics of intonation and its implications in In the poem "The Poet and the Unjust King" poem by Ilia Abi Madi
مقال . القارئ للدراسات الأدبية والنقدية واللغوية . مج 06 . ع 03 جامعة الوادي
Keywords: إلايقاع؛ التنغيم؛موسيقى الشعر؛الجماليات؛ إليا أبو ماض ي; tempo; toning; poetry music; aesthetics; Elia Abu Madi.